Analisis Pengaruh Nilai Rasa Makanan Terhadap Sikap Turis Pada Makanan Lokal Padang - Kahar, Azmen (Jurnal Bisnis Digital dan Enterpreneur (BISENTER), 2023)
The purpose of this study was to analyze the effect of food taste scores on tourists' attitudes towards local food in Padang. This type of research is a causal research that examines the effect of the independent variable, namely the value of food taste on the dependent variable, namely the attitude of tourists towards local food in Padang. The respondents of this study were tourists who visited the tourist area of the city of Padang. Determining the number of samples using purposive sampling technique, not less than 200 respondents. The data analysis technique used is path analysis which is useful for determining to analyze the effect of causal variables on effect variables either directly or indirectly. The results of the study show that the taste value of food has a significant effect on tourists' attitudes towards local food in Padang.